Generation Sustainability Strategy Through Gamification Learning: A Study of the Influence of Habits of Mind and Mathematics Interest on Decision-Making Ability - Wasilatul Murtafiah; Ruina Nur Fitria; Restu Lusiana; Marheny Lukitasari; Nurcholif Diah Sri Lestari; Joel I. Alvares (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
This research was motivated by students' lack of interest and response to learning mathematics. Based on findings in the field, it was found that students still considered mathematics a scourge and the most boring subject. This study aims to determine the influence of habits of mind and mathematics interest on students' decision making through gamification learning. This is a correlational research ex post facto quantitative approach using double linear regression. The data were obtained through questionnaires and tests. The research was conducted at SMKN 1 Geger, Madiun, East Java, with research subjects consisting of students of class XI Islamic Banking 1 and class XI Automation of Office Management 1. The results showed that habits of mind and mathematics interest significantly positively affected students' decision making in mathematics through gamification learning.